1999
DOI: 10.1063/1.124769
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of C60 films in the high-temperature region

Abstract: Articles you may be interested inMicrowave dielectric properties of tunable capacitors employing bismuth zinc niobate thin films

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…57,58 The capacitance increase was also interpreted as arising from an increase in the number of charge carriers and enhancement of the carrier hopping between localized traps (i.e., increase of conductivity) with increasing temperature. 58,59 Furthermore, the above capacitance-increasing effects were shown to be dependent upon frequency; the capacitance was observed to attain high values in the quasi-static limit of low frequencies, decrease rapidly at frequencies above 100 Hz, and attain a constant value at higher frequency. [56][57][58] The dielectric constant ε of asphaltenes was regarded as equivalent to the real part of the complex relative permittivity ε 0 in the frequency-independent range (6-35 °C) of Figure 12.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…57,58 The capacitance increase was also interpreted as arising from an increase in the number of charge carriers and enhancement of the carrier hopping between localized traps (i.e., increase of conductivity) with increasing temperature. 58,59 Furthermore, the above capacitance-increasing effects were shown to be dependent upon frequency; the capacitance was observed to attain high values in the quasi-static limit of low frequencies, decrease rapidly at frequencies above 100 Hz, and attain a constant value at higher frequency. [56][57][58] The dielectric constant ε of asphaltenes was regarded as equivalent to the real part of the complex relative permittivity ε 0 in the frequency-independent range (6-35 °C) of Figure 12.…”
Section: Resultsmentioning
confidence: 96%
“…In the “hot” phase, π interactions among aromatic moieties predominate and the dipolar segments become more flexible. Enhancement of temperature-sensitive π−π bonding between condensed aromatic systems was observed to increase the measured capacitance, while the increase of bound dipole flexibility in organic materials is frequently cited as a cause of the capacitance rise with the temperature. , The capacitance increase was also interpreted as arising from an increase in the number of charge carriers and enhancement of the carrier hopping between localized traps (i.e., increase of conductivity) with increasing temperature. , Furthermore, the above capacitance-increasing effects were shown to be dependent upon frequency; the capacitance was observed to attain high values in the quasi-static limit of low frequencies, decrease rapidly at frequencies above 100 Hz, and attain a constant value at higher frequency. …”
Section: Resultsmentioning
confidence: 96%
“…From the specific heat data, a phase transition at 425 K has already been observed in the C 60 crystal 1) and also internal friction measurements of the crystalline C 60 film have detected a -shaped peak at 426 K. 2) Raman scattering measurements have shown that interaction between the molecules in the C 60 crystal become isotropic at temperatures above 400 K. 3) Vickers hardness study has also shown that, hardness of C 60 crystals decreases rapidly when temperature is above 425 K. 4) Carbon-13 ( 13 C) nuclear magnetic resonance (NMR) spectrum of crystalline C 60 reveals that magnetic shielding anisotropy dominates in the temperature range of 100 -340 K [5][6][7][8] and is dependent of the spin-rotation interaction above 400 K. 9,10) Measurement of the electrical properties of C 60 crystals has indicated that the dissipation factor has a peak around 435 K, 11) and an anomaly in the electrical conductivity at 450 K. 12) In addition, X-ray diffraction (XRD) analysis has shown that besides the face-centered cubic (fcc) phase, there also exists a hexagonal close packed (hcp) phase between the fcc crystallites in the C 60 solid. 13,14) The hcp phase is unstable at high temperatures, and disappears after annealing above 453 K. 15) In this study we have observed an abnormal temperature dependence of the conductivity of the C 60 solid in the temperature range of 400 -500 K. We will show evidences that both molecular rotation and crystallinity of the C 60 solid results in the abnormal temperature dependence of the conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant to these results are prior studies indicating that solid C 60 arrays rotate almost freely in a rotationally disordered high‐temperature, face‐centered cubic phase (above 260 K at atmospheric pressure). This motion is said to slow down and is transformed into a ratcheting or rocking motion in an orientation‐ordered simple cubic phase at low temperatures and high pressures . Su et al demonstrated a structural phase transition at 260 K as well as an anomaly at 90 K resulting from a glass transition.…”
Section: Resultsmentioning
confidence: 99%
“…This motion is said to slow down and is transformed into a ratcheting or rocking motion in an orientation-ordered simple cubic phase at low temperatures and high pressures. [38][39][40] Su et al 38,39 demonstrated a structural phase transition at 260 K as well as an anomaly at 90 K resulting from a glass transition. Furthermore, these investigators observed a Debye-like relaxation in the dielectric response, e 0 and tan d versus f curves at three temperatures for C 60 (OH) 29 and Sc 3 N@C 80 (OH) 18 are provided in Figures 3 and 4, respectively.…”
Section: Resultsmentioning
confidence: 99%